(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Dividend policy connexion has been researched extensively, however very little agreement has been designed from the findings. There are several factors that have an effect on a given firm’s dividend policy which might be found within the literature like risk sweet-faced by the firm, income state of affairs of the firm, agency prices etc. per Bhattacharya (1979) dividend call of a firm may be seen as a supply of signal that shows that profitable corporations with sensible project investment opportunities can pay higher dividends to gift themselves distinct from different firms which are having comes with lesser profits. This paper makes a trial to analyze whether or not or not the dividend policy of a firm affects the market value of a firm and so the shareholders’ wealth. We’ve set our objective to search out the impact of dividend policy on the shareholders’ wealth within the Indian electrical instrumentality producing trade. For this, we’ve adopted a sample of dividend paying electrical machinery producing corporations listed in urban center stock market (BSE). There have been all 439 corporations within the trade of electrical machinery producing. Out of them 194 corporations were listed within the urban center stock market (BSE) and there have been seventy two companies paying dividends often. So the info of those seventy two corporations was taken into thought. Our study unconcealed the empirical proof with a number of the dividend unconnectedness theories like MM. The results indicate that there’s a negative non-linear association between the value of a share and thus the dividend yields of the trade.